Development of Mahabharata teaching materials for Hindu character education in SMAN 3 Denpasar - Trimo; Winaja, I Wayan; Suasthi, I Gusti Ayu (Indonesian Journal of Educational Development (IJED), 2025)
Character education plays a vital role in shaping students' values, yet many existing materials in Hindu Religious Education fail to integrate moral teachings effectively. The Mahabharata, a classical Hindu epic, offers rich narratives that support value-based learning. This study aims to: (1) assess the need for Mahabharata-based teaching materials that incorporate Hindu character values, (2) develop such materials through a structured process, and (3) evaluate their impact on the quality of learning at SMAN 3 Denpasar. Using a Research and Development (R&D) design adapted from Borg and Gall, the study involved needs analysis, expert review, limited and full-scale trials, and product refinement. Instruments were validated for reliability, and data were analyzed using descriptive statistics and t-tests. Findings indicate that the developed materials improved students’ engagement and understanding of dharmic values. The study recommends implementation of these modules in classroom practice and suggests broader integration of culturally rooted texts into the national character education curriculum.